Lembaga Dakwah dan Wasatiyah: Sebuah Tela’ah Perspektif Manajemen Dakwah di Kota Salatiga - Yahya Yahya (IAIN Salatiga, 2019)
This study aimed to determine the understanding of the Salatiga preaching institution to wasatiyah, the management of preaching in preaching wasatiyah, and the obstacles. The research used was a qualitative method. The results of this study indicated that the understanding of da’wah institutions to wasatiyah could be said to be linear. There was a tendency to equate moderate wasatiyah and a tendency to reject the radical, rigid, violent, and ghuluw religious methods and are felt to be lacking when rejecting the tafrīt or taqsīr or jafā ’religion. The preaching management of the Da’wah preaching institution in Salatiga was still natural in nature and was a routine activity that had not approached the ideal management in the preaching of uncertainty in determining its vision and mission in preaching Wasatiyah. And the obstacles were the different perspectives of management, limited human resources, limited infrastructure and financial advice, ego and rigidity of some administrators